2015
DOI: 10.1108/ijchm-08-2013-0350
|View full text |Cite
|
Sign up to set email alerts
|

Differences in service quality perceptions of stakeholders in the hotel industry

Abstract: Purpose – Studies in the service quality evaluation literature have generally attempted to determine the service quality perception level of customers by mainly focusing on customers’ quality evaluations. However, the nature and characteristics of differences in service quality perceptions among customers, managers and employees are not sufficiently researched. In this study, the differences in service quality perceptions among the aforementioned stakeholders are examined. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
1
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(83 citation statements)
references
References 83 publications
(94 reference statements)
3
74
1
5
Order By: Relevance
“…Izogo and Ogba (2015), Dedeoğlu and Demirer (2015) and Zamil, Areiqat and Tailakh (2012) all found the same results. In contrast, Qin, Prybutok and Zhao (2010) found that only three attributes, tangibles, reliability and responsiveness, were particularly salient dimensions in fast food restaurants in China.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…Izogo and Ogba (2015), Dedeoğlu and Demirer (2015) and Zamil, Areiqat and Tailakh (2012) all found the same results. In contrast, Qin, Prybutok and Zhao (2010) found that only three attributes, tangibles, reliability and responsiveness, were particularly salient dimensions in fast food restaurants in China.…”
Section: Discussionsupporting
confidence: 71%
“…Convergent validity was tested by calculating the average variance extracted (AVE) by each factor. The results for convergent validity presented in Table 2 indicate that the variance for each factor is greater than the minimum recommended standard of 0.50 (Dedeoğlu & Demirer, 2015), which means that the convergent validity of the measurements is verified. The square root of AVE was used to examine discriminant validity.…”
Section: Validity and Reliability Of The Instrumentmentioning
confidence: 93%
See 2 more Smart Citations
“…Adding to the dilemma, this industry sometimes falls short of being able to measure the value of public relations to their business (Lymperopoulous, Chaniotakis & Soureli, 2006) [33]. As explored in the vast literature, various authors have already examined service quality, food quality and customer satisfaction constructs in different settings in different countries, such as in the healthcare industry (Yeşilada & Direktör, 2010)[50], the hotel industry (Dedeoğlu & Demirer, 2015) [17], retail settings (Anselmsson & Johansson, 2014[6]; Omar, Shaharudin, Jusoff, & Ali, 2011), tourism industry (Debata, Patnaik, Mahapatra, & Sree, 2015 [16]; Al-Tit & Nakhleh, 2014) [4], the gaming industry (Wu, 2014), as well as the food industry (Marinelli, Simeone, & Scarpato, 2015 [34]; Wang, 2015 [46]; Kafetzopoulos, Gotzamani, & Psomas, 2014 [28]; Bujisic, Hutchinson, & Parsa, 2014 [13]; Jang & Ha, 2014; Wettstein, Hanf, & Burggraf, 2011) [47]. Hence, the growing number of studies devoted to such topics that are being published is a clear evidence to the increased importance of these constructs.…”
Section: Introductionmentioning
confidence: 99%